Civil action for rape in Malaysia / Najmu Fatihah Mohd Zin … [et al.] - Mohd Zin, Najmu Fatihah; Baharim, Norhidahayu; Abu Zarim, Nur Aina; Amir Shariffuddin, Sharifah Amirda Shasha (Faculty of Law, 2013)
This research paper analyzed on the viability of implementing civil action for rape in Malaysia with references made to other countries: the United States, the United Kingdom and, Canada. Basically in Malaysia, there were rarely civil actions taken for the crime of rape unlike in the Western Countries. This research paper is to help understanding the civil action for rape better and to determine the viability of taking such action in Malaysia. Based on the research done, some recommendations were made with the intention to improve the position of victims of rape when it comes to getting monetary compensation. The first chapter goes into the essences and the structures of the research. In the second chapter, it focused on the position of law in Malaysia regarding compensating victims of rape, the advantages of taking civil action for rape and also, the disadvantages of taking such action. The third chapter discussed on the position of civil action for rape in the United States, the United Kingdom and, Canada. Apart from that, Chapter Four lays out findings of the research based on several interviews conducted. Lastly, Chapter Five provides the conclusion and also some recommendations for the implementation of civil action for rape in Malaysia